A Study of the Granulomatous Responses Induced by Different Strains of Schistosoma mansoni. (5th November 2012) - Zuim, Nádia Regina Borim; Allegretti, Silmara Marques; Linhares, Arício Xavier; Magalhães, Luiz Augusto; Zanotti-Magalhães, Eliana Maria
Abstract : The increased pathogenesis of the Schistosoma mansoni BH strain compared with the SJ strain has been attributed to the number of granulomas formed in experimental infections, which increase the mortality in definitive hosts. The aim of the present study was to investigate the development of granulomas around the eggs of the S. mansoni BH and SJ strains and to determine whether this host reaction was strain specific. Four experimental groups were analyzed. Two groups contained mice inoculated in the caudal vein with eggs from the S. mansoni BH or SJ strains and the other two contained mice that were infected with cercariae of the BH strain prior to being inoculated with eggs. The number of granulomas per tissue area in the lungs and liver, as well as the size of the granulomas, was analyzed to characterize the response to schistosome infection. The largest granulomatous responses were observed around eggs of the BH strain. Granulomas covered a larger area in the lungs of mice that were previously infected with cercariae and subsequently inoculated with eggs of the BH strain. These results indicated that specific granulomatous responses occurred following an infection with the BH and SJ strains of S. mansoni .